2002
DOI: 10.1890/0012-9658(2002)083[0148:teosaa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Slavemaking Ants and Their Hosts in North Temperate Forests

Abstract: Slavemaking ants are of great interest to biologists because of their highly specialized lifestyle. Slavemakers rely on the presence of heterospecific ''slaves'' to perform routine chores such as foraging and brood care. While we have considerable information on the behavior of these ants, mostly gleaned from laboratory studies, we know very little of their basic ecology. Here we report data collected over 20 yr in three geographic sites on the occurrence, spatial pattern, nest site use, and demography of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(107 citation statements)
references
References 53 publications
11
95
1
Order By: Relevance
“…Whenever possible, we therefore included long-term collection data on parasite pressure from previously studied communities (i.e. Ohio North, West Virginia, Vermont and New York [23][24][25][26]). Moreover, we have evidence for consistent parasite occurrence from some other communities that have been sampled sporadically in the past (i.e.…”
Section: (B) Parasite Pressure Estimatesmentioning
confidence: 99%
“…Whenever possible, we therefore included long-term collection data on parasite pressure from previously studied communities (i.e. Ohio North, West Virginia, Vermont and New York [23][24][25][26]). Moreover, we have evidence for consistent parasite occurrence from some other communities that have been sampled sporadically in the past (i.e.…”
Section: (B) Parasite Pressure Estimatesmentioning
confidence: 99%
“…The evolutionary repercussion of being weakly adapted to multiple target species is the diminished rate and probability of fixing beneficial alleles or purging deleterious ones (Kawecki 1994, Whitlock 1996. Thus, variation in target species is capable of producing selection mosaics that differ in intensity and have variable coevolutionary outcomes (Thompson 1994, Thompson and Pellmyr 1992, Gomulkiewicz et al 2000; e.g., Benkman et al 2001, Foitzik et al 2001, Foitzik and Herbers 2001a, Herbers and Foitzik 2002. This is also true for systems with multiple enemies and a single target species (e.g., Wissinger and McGrady 1993, Benkman 1999, Siddon and Witman 2003, but most of these studies focus on the effect of multiple predators on a single prey whereas interactions between parasites are only just emerging as determinants of community dynamics (Poulin 1998).…”
Section: Introductionmentioning
confidence: 99%
“…If slavemaker brood rarely survives, slavemaking colonies remain small and nearby host colonies, which are potentially related to the slaves in the slavemaker nest, will experience a reduced raiding risk. The severe reduction in parasite brood survival presents an explanation why slavemaker nests of P. americanus are exceptionally small compared to nests of related species (Foitzik and Herbers 2002). The strong differences we find in brood survival between the three habitats suggest that these communities are at different stages in a coevolutionary arms race or that the costs/benefit trade-off for the trait differs between sites.…”
Section: Discussionmentioning
confidence: 69%
“…One potential explanation of the observed low survival of slavemaker pupae could be that it is a laboratory artefact, which is not relevant under natural conditions. However, earlier studies found very low per-worker-productivity in parasite nests under field conditions (Foitzik and Herbers 2002) indicating similarly low survival rates in the field. Secondly, the observed low survival of slavemaker pupae could be the result of enslaved workers generally caring less well for allospecific brood compared to conspecific brood.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation